Pola konsumsi makanan di luar rumah sebagai faktor risiko terjadinya obesitas pada remaja SMP di Kota Palembang - Podojoyo Podojoyo; Hamam Hadi; Emy Huriyati (Jurnal Gizi Klinik Indonesia, 2006)
Background: Teenagers nutriture are complicated because teenagers often ignore meal time, have snacks and do not eat regularly so that eating out such as having fast foods becomes a favorite choice. Prevalence of obesity among teenagers in Yogyakarta is 7.8%, Tangerang 5.01% and Surabaya 6.5%. Changes of eating pattern in the family and habit of eating out at restaurants or food courts are presumed as factors that increase prevalence of obesity at Palembang Municipality.Objectives: To explore  prevalence of obesity and identify relationship of eating out pattern among obese and non obese junior high school teenagers at Palembang Municipality.Method: First, a survey was done to 1,300 junior high school teenagers at Palembang Municipality to find out prevalence of obesity using cross sectional design with cluster random sampling technique. Next, to find out relationship between eating out consumption pattern and obesity, case control study with simple random sampling technique was used. Total number of samples in case control design was as many as 174 people, matched with age, sex, and grade. The study was conducted in July–December 2005. Data were analyzed using univariable, bivariable, and multivariable techniques.Results: Prevalence of obesity among junior high school teenagers at Palembang Municipality was 6.62%. There was no significant relationship (p>0.05) between eating out fre- quency, consumption of energy, protein, fat and carbohydrate, and occurence of obesity. There was significant relationship  (p<0.05) between total consumption of energy, fat, carbohydrate, frequency of eating in, obese status of parents, social economic status of the family, education of fathers and mothers, and occurence of obesity. Conclusions: Factors related to occurence of obesity were frequency of eating in, total consumption of energy, obese status of parents and education of fathers. The factor most dominantly related to obesity was frequency of eating in.